The analysis of motor ability of physical education students - Zulrafli; Kamarudin (Journal Sport Area, 2021)
In producing good and quality learning in physical education, it needs to be equipped with the right motoric movements to achieve goals and follow the learning contained in the physical education curriculum so that the graduates expected can be completed. This study aims to determine the motoric skills level of physical education students in Universitas Islam Riau. This research is a quantitative descriptive study. The method used is a survey method in the form of tests and measurements for physical education students. The population used in this study is all physical education students in semester 1 of the 2019/2020 academic year, with a total of 224 people. The sample is 144 people selected by random sampling. The instrument used was the motor ability test from Harol M. Barrow in the form of a test battery with a validity coefficient of 0.92 with a series of tests; a) Standing Broad Jump, b) Wall Pass, c) Medicine Ball-Put, d) 60 Yard Dash. The research results on the level of motor skills of physical education students at Universitas Islam Riau were mostly in the medium category. Furthermore, from the results of this study, it is necessary to pay more specific attention to physical education students' motor abilities. Because with good motor skills, someone can do various kinds of movements in sports and the courage to do multiple sports activities.